235k views
16 votes
I would very appreciate help with this pretty soon.

I would very appreciate help with this pretty soon.-example-1
User Lon Kaut
by
5.4k points

2 Answers

1 vote

Answer:

Step-by-step explanation: Hi there.

We can treat this problem just like a simple subtraction problem, like 3-2

It helps to form the equation like this:

x^2+9x+18

- (1x+06)

Remember that the operation changes the sign: -1x-6

The result is x^2+8x+12, and it is already in standard form.

Have a nice day! :)

User GWigWam
by
4.6k points
11 votes

Answer:

x² + 8x + 12

Step-by-step explanation:

given:

  • f(x) = x² + 9x + 18
  • g(x) = x + 6

solve function:

→ f(x) - g(x)

→ x² + 9x + 18 - (x + 6)

→ x² + 9x + 18 - x - 6

→ x² + 9x -x + 18 - 6

→ x² + 8x + 12

User Happygoat
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.